Education Profiling for East Java Student-Athletes: Planning, Process, Assessment, and Expectations - Suroto, Suroto; Kusnanik, Nining Widyah; Pradana, Febryansah Gilang Aris; Prakoso, Bayu Budi; Bafirman, Bafirman; Barlian, Eri; Usman, Arifuddin; Arimbi, Arimbi; Sumaryanti, Sumaryanti; Wijaya, Made Agus (Faculty of Sport and Health Sciences, 2024)
Dual-career student-athletes must be supported by rigorous training and academic processes that suit their needs. Unfortunately, student-athletes' academic performances are not as satisfactory as their sports achievements. Their sports training and the academic process are needed. This qualitative study aimed to analyze the academic services student-athletes receive from faculty and their expectations. A total of 30 studentathletes who had achieved sports achievements at regional, national, and international levels were interviewed about academic services ranging from planning, materials, learning processes, assessment, and expectations. The data were analyzed using the NVivo application. The findings of this study are that student academic services are stated to be the same between student-athletes and non-athletes. The faculty has provided special licensing services for student-athletes; there needs to be a better alignment of faculty and lecturer-level licensing. Student-athletes feel that the allocation of academic activities needs to be lowered, assignments are not by theconditions of student-athletes, and students need special athlete classes that are flexible to rigorous sports activities